1975
DOI: 10.1002/tea.3660120405
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of science subject matter and developmental levels of learners

Abstract: IntroductionAccording to the Piagetian model, formal thought begins to develop at age 11 or 12 and reaches an equilibrium state at around age 15 or 16. This model states that concreteoperational persons are unable to develop understanding of abstract concepts, i.e., concepts which require the building of theories and departures from concrete reality (Inhelder & Piaget, 1958. pp. 339-342). Also, it is implied that formal-operational persons are able to develop understanding of both concrete and abstract concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
2
11

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 10 publications
6
89
2
11
Order By: Relevance
“…This mean score indicates that, on the average, the students are operating at the late concrete or transitional level. These results do not differ from those of previously studied Caucasian college students (Lawson and Renner, 1975). Note: "C" designates a complex problem.…”
Section: Analysis and Resultssupporting
confidence: 54%
“…This mean score indicates that, on the average, the students are operating at the late concrete or transitional level. These results do not differ from those of previously studied Caucasian college students (Lawson and Renner, 1975). Note: "C" designates a complex problem.…”
Section: Analysis and Resultssupporting
confidence: 54%
“…Scientists use a general theory or idea to move through a sequence of ideas and arrive at specific conclusions. Gipson, Abraham & Renner (1989) and Lawson & Renner (1975) contended that solving and interpreting genetics problems involves formal-level operations such as combinatorial, proportional, and probabilistic reasoning, which is consistent with Piaget's developmental theory. Cavallo (1996) reported that students' reasoning ability can predict their performance in solving genetics problems.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 64%
“…"The term postulatory-deductive refers to the theoretical models (systems) of science. Meaning is given to these concepts not through senses but through imagination or through their logical relationship with the system" (Lawson, 1975).…”
Section: Logical Thinking (Lth)mentioning
confidence: 99%